HUBUNGAN POSISI DUDUK DAN LAMA DUDUK PADA NYERI PUNGGUNG BAWAH - Birman, Yuliza; Rinaldi, Arief; Luqmanul Insan Fadhil, Aulia (Nusantara Hasana Journal, 2026)
Lower Back Pain (LBP) is a common musculoskeletal problem experienced by many people, including students who have the habit of sitting for long periods. This condition can interfere with daily activities and the quality of students' lives. The high global prevalence of LBP highlights the urgency to understand the risk factors of LBP. Sitting habits with non-ergonomic positions and prolonged sitting durations have been identified as potential contributors to the development of LBP in students, which can negatively impact academic activities. Objective: To determine the relationship between sitting position and duration with complaints of lower back pain among students of the Faculty of Medicine at Baiturrahmah University. Methods: This study used an analytical method with a cross-sectional study design. The study respondents consisted of 91 medical students at Baiturrahmah University, selected using consecutive sampling technique. Data collection was conducted using the RULA questionnaire instrument and The Pain and Distress Scale. The data analysis used was the chi-square test. Results: From 91 student samples from the Faculty of Medicine at Baiturrahmah University, the majority of respondents were 21 years old (61.5%), with females being the most common gender (56%), and having a normal BMI (50.5%). Most had a very high-risk sitting posture (47.3%) and sat for more than 4 hours/day (83.5%). The majority of those experiencing lower back pain were in the mild category (86.8%). Statistical analysis showed a significant relationship between sitting posture and lower back pain (p-value=0.015) and between prolonged sitting duration and lower back pain (p-value=0.025). Conclusion: Based on the analysis above, it can be concluded that there is a relationship between sitting posture and prolonged sitting duration with lower back pain in students of the Faculty of Medicine at Baiturrahmah University.